'Planning Your Neighbourhood': modernism on manoeuvres. Issue 4 (December 2020) - Mills, Stuart
Abstract : In the summer of 1945, Ernö Goldfinger produced a twenty-sheet exhibition entitled 'Planning Your Neighbourhood' (PYN) for the Army Bureau of Current Affairs (ABCA) [1]. It shows how Goldfinger continued to promote a vision of modern architecture that had evolved in the 1930s, by adapting it to planning for postwar urban reconstruction. The reach of PYN went beyond that of a public exhibition because of its role in Army education; for the majority of its audience it wasn't a matter of choice – the sheets were brought to them. This article examines the strategies he adopted to communicate the validity of modernism in Britain. It will show how wartime circumstances provided Goldfinger with a remarkable opportunity to present modern architecture to a mass audience.